(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The rare and localyzed species Cryptocephalus barii Budini, is recorded from Mount Grigna Settentrionale (Lombard Pre-Alps). Some ecological information and the drawing of the spermatheca are also given.